Nikoides schmitti Manning & Chace, 1971 (Caridea: Processidae) in the South Atlantic Ocean, with an updated list and key for processid shrimps of Brazil - Almeida, Alexandre Oliveira; Bezerra, Luis Ernesto Arruda (Zootaxa, 2011)
The shrimp Nikoides schmitti Manning & Chace, 1971 (Decapoda: Caridea: Processidae) is reported for the first time from the South Atlantic Ocean, based on four specimens dredged on soft bottoms of the continental shelf of the Camamu Basin, Bahia, Brazil (13°28’–13°30’S; 38°47’–38°49’W), at a depth range of 38–49 m depth. The Brazilian material is illustrated and an updated list of the Brazilian processid shrimps and a key for their identification are provided.